The role of information in technology adoption under poverty - Jinhua Zhao (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
An important channel through which globalization affects poverty is introducing new technologies to developing countries. Adoption of new technologies can be hindered by uncertainties about their efficiency. This paper studies the role of information exchange between adopters and others about a new technology and about each other's likelihood of adoption. We show that information about the technology can reduce adoption at the beginning of the diffusion process and increase adoption later. Information about each other increases adoption at the beginning and reduces adoption later on. We also discuss ways to promote adoption, including initial information provision, timing communication about the technology and about each farmer, and compensating early adopters for their information services. – ICT ; diffusion ; globalization ; econometric methods
Keywords: O33; C11; I32; 330; Armut; Technischer Fortschritt; Informationstechnik; Informationsverbreitung; Entwicklungsländer